Analysis of NOS (Nature of Science) and STEM (Science, Technology, Engineering & Mathematics) Aspects in High School Biology Textbooks of The Merdeka Curriculum Phase E - Jalmo, Tri; Agus Priadi, Median; Laila Safitri, Aulia; Jaya Putra , Dani (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study aims to analyze the levels of the Nature of Science (NOS) and STEM aspects in the Merdeka Curriculum Phase E High School Biology textbooks. This study employs a simple descriptive research design. The data consists of qualitative and quantitative information. Data collection was conducted using documentation techniques. Data analysis utilized descriptive statistical techniques with percentage formulas and was described based on categorical levels. The results indicate that the average level of the NOS aspects in the three textbooks is categorized as 'Adequate', with Book A at 42.2%, Book B at 43.9%, and Book C at 41.9%. Meanwhile, the average level of the STEM aspects in the three textbooks is categorized as 'Poor', with Book A at 32.8%, Book B at 24.8%, and Book C at 30.5%. This study highlights the need to improve the integration of NOS and STEM aspects in the Merdeka Curriculum Phase E Biology textbooks to support the learning process with students. Analisis Aspek NOS (Nature of Science) dan STEM (Science Technology Engineering Mathematics) pada Buku Biologi SMA Kurikulum Merdeka Fase E ABSTRAK: Penelitian ini bertujuan untuk menganalisis tingkat aspek NOS dan STEM pada Buku Ajar Biologi SMA Kurikulum Merdeka Fase E. Penelitian ini merupakan penelitian deskriptif sederhana. Data penelitian ini berupa data kualitatif dan kuantitatif. Pengumpulan data dilakukan dengan teknik dokumentasi. Analisis data dilakukan dengan teknik statistik deskriptif menggunakan rumus persentase dan dideskripsikan berdasarkan tingkat kategori. Hasil penelitian menunjukkan rata-rata tingkat aspek NOS pada ketiga buku ajar tergolong ‘Cukup Baik’ dengan persentase buku A sebesar 42,2%, buku B sebesar 43,9%, dan buku C sebesar 41,9%. Kemudian rata-rata tingkat aspek STEM pada ketiga buku tergolong ‘Buruk’ dengan buku A sebesar 32,8%, buku B sebesar 24,8%, dan buku C sebesar 30,5%. Dari penelitian ini menunjukkan perlunya peningkatkan muatan aspek NOS dan STEM pada buku ajar Biologi Curriculums Merdeka Fase E untuk mendukung proses pembelajaran dengan peserta didik.